Implementasi Pengelolaan Barang Milik Daerah Kota Pekanbaru Melalui Aplikasi LAKSAMANA (Lintas Aplikasi Data Manajemen Aset) - Adlin; Darmansyah, Ramlan; Rizki, Nanda (LPPM STISIP IMAM BONJOL, 2025)
Implementation of Pekanbaru City Regional Property Management within the Pekanbaru City Government is carried out, through the Cross Application Data Asset Management application system to facilitate inventory data collection and management of Regional Property which is an asset of the Pekanbaru City Government. The problems in this writing are still many Regional Property Items in Pekanbaru City Regional Apparatus that have not been properly managed and recorded. The method used in this writing is descriptive qualitative by describing phenomena and data obtained from document sources, mass median and journal. The results of the discussion in this writing are that in collecting data on the inventory of Regional Property in Pekanbaru City Regional Apparatus, has been carried out well, however There are still several Regional Apparatuses who have not achieved the inventory progress target. Furthermore, the Pekanbaru City Asset Management Data Cross Application was used by all Pekanbaru City Regional Apparatus properly.